The structure of production in Greek agriculture: Elasticities of substitution and derived factor price elasticities - Melfou, Katerina; Theocharopoulos, Athanasios; Papanagiotou, Evangelos (SPOUDAI Journal of Economics and Business, 2008)
The objective of this paper is to measure the own price, the cross price elasticities of derived input demand and the Allen-Uzawa elasticities of substitution among input pairs for the Greek agricultural sector. A restricted cost function is used to approximate agricultural technology and two quasifixed inputs are included, which are capital and a detrimental or ‘nonproductive’ input, namely nitrate pollution. The system which consists of the translog cost function, factor share equations and a revenue share equation is estimated by the method of Seemingly Unrelated Regressions. Findings indicate that demand is price inelastic for the three variable inputs. Labour is found to be a substitute for land and for intermediate inputs. Land and intermediate inputs are complements. JEL Classifications: Q11, Q12